(untitled) (Bangladesh Journal of Medical Science, 2023)
Introduction: The outbreak of COVID- 19 has caused a significant impact on the world’s population. This study examines the impact of COVID-19 on the level of depression, anxiety and stress among students of National Defence University of Malaysia (NDUM), and to assess coping styles during this critical time. Methods: This was a cross-sectional study conducted during the Conditional Movement Control Order (CMCO) on May 2020 during the COVID-19 pandemic. DASS-21 and BRIEF COPE were used as the assessment toolsfor this study. Data was analysed using descriptive statistics, Independent T-test and One-way ANOVA with comparisons of multiple variables using post-hoc Tukey’s test. Results: A total of 603 participants were included in the study. Respondents’ mean age was 21.06 ± 1.75. They consisted of 52.6% male, 86.9% Malays and 76.9% non-cadets. The prevalence of depression, anxiety and stress were 51.9%, 46.9% and 18.7% respectively. Female, those who are from the Language Centre and non-cadet students, showed a statistically significant higher score of depression, anxiety and stress. A high-stress score was seen in Bachelor degree students compared to Foundation students. Those with no financial sponsorship showed the highest anxiety score. The most common coping style used among the respondents was religion and the least is substance abuse. Conclusion: This study has identified the risk groups for developing psychological distress during times of crisis. Thus, there is an urgent need to address the concern on mental health and provide a structured support for them. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 105-114